An Analysis of Lexical Cohesion on the Students’ Writing - Usman Sidabutar (English Education Department at FKIP Nommensen University, 2021)
This research aims at finding lexical cohesion in high and low-graded lexical cohesion types on the students' narrative writing. The researcher wants to reveal the reasons why the writing problems exist in lexical cohesion and also to find out what way that the students will use to solve the lexical types in writing narrative text. The present research uses the types of lexical cohesion as proposed by Halliday and Matthiensen (2014). The lexical cohesion items consist of repetition, synonymy, antonymy, hyponymy, and meronymy. The data of this research are derived from students' writing through writing research papers. This research was conducted in qualitative. The results show that repetition becomes the highest occurrence in the students' writing as there are 240 occurrences (64%) in total types of lexical. Nevertheless, the least kind of lexical cohesion is hyponymy. There are only 20 occurrences (6, 6%). It can be seen that the meaning relation in the text occurs among the six types of lexical cohesion to make cohesive text. Besides that, the context of the text itself also refers to coherent text. It means that the text should consist of interrelated sentences to achieve good unity. Both are related to each other in creating well-structured text. The students were sometimes difficult to connect one word with other words. There might be a reluctance of translating the classification of the real words of EFL. Pedagogically, the students need to get studying vocabularies professionally to upgrade the stage of English into an advanced level especially in teaching English writing ability. It was recommended to teachers or lecturers to take an in-depth look at the EFL learners' problems in writing English more than and the English lecturers practice the prompt way to master vocabulary as the core of enhancing the writing quality